Production of β‐carotene with Dunaliella salina CCAP19/18 at physically simulated outdoor conditions - Lara Wolf; Thomas Cummings; Katharina Müller; Manfred Reppke; Marianne Volkmar; Dirk Weuster‐Botz (Engineering in Life Sciences, 2021)
Abstract Batch growth and β‐carotene production of Dunaliella salina CCAP19/18 was investigated in flat‐plate gas‐lift photobioreactors with a light path of 2 cm, operated in physically simulated outdoor conditions. Dunaliella salina CCAP19/18 showed robust growth with respect to pH 8.0‐9.0 and 15–35°C at increasing salinity, simulating the evaporation of open photobioreactors. The highest β‐carotene concentration of 25 mg L‐1 (3 mg gCDW−1) was observed in batch processes at pH 8.5, 15–30°C and increasing salinity up to 110 g L‐1, simulating a typical Mediterranean summer climate. Intracellular β‐carotene accumulation of D. salina CCAP19/18 was shown to be independent of light availability, although nutrient limitation (K2HPO4, MgSO4, and/or ammonium ferric citrate) seems to enable stable β‐carotene content in the algal cells despite increasing cell densities in the photobioreactor. Fully controlled, lab‐scale photobioreactors simulating typical climate conditions of any region of interest are valuable tools for enabling a realistic characterization of microalgae on a laboratory scale, for production processes projected in open photobioreactor systems (e.g. thin‐layer cascade photobioreactors).